Smart preparation of CNT-filled conductive polymer nanocomposites - Poh, Yueh Loong. (2013)
This final year project is to fabricate polymer nano-composite with poly(methyl methacrylate) (PMMA) as the polymer matrix, multi-walled carbon nanotubes (MWCNTs) and silicon dioxide (SiO2) as the reinforcement fillers. The objective of this project is to determine if the addition of non-electrical conductive SiO2 will increase the electrical conductance of the polymer nano-composite while keeping the content of the electrical conductive carbon nanotubes (CNT) a constant. The technique of solution mixing was employed to fabricate thin films of polymer nano-composite samples, while using acetone as a solvent to dissolve PMMA and ultrasonication was used for the even dispersion of CNT and SiO2. The fabricated composite samples were characterized by SEM and FESEM. The SEM images showed an even dispersion of SiO2 particles in the composite sample while the FESEM images illustrated an improvement in the electrical connection between the CNTs due to the addition of SiO2. The results showed a constant decreasing trend of the electrical resistance of the samples when the content of SiO2 was increased in the composite while keeping the content of CNT constant, which proved the effectiveness of the SiO2 to increase the electrical conductance of the polymer nano-composite.